2020
DOI: 10.1088/1674-1056/ab8205
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies on ammonium iodine under high pressure*

Abstract: Ammonium iodine (NH4I) as an important member of hydrogen-rich compounds has attracted a great deal of attention owing to its interesting structural changes triggered by the relative orientations of adjacent ammonium ions. Previous studies of ammonium iodide have remained in the low pressure range experimentally, which we first extended to so high pressure (250 GPa). We have investigated the structures of ammonium iodine under high pressure through ab initio evolutionary algorithm and total energy calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…The band gap value increases rst and then decreases when the P 43m phase transforms into the P4/nmm phase, which is identical to that found in NH 4 I. 15 In the pressure range of phase IV, the band gap increases with increasing pressure, which also occurs in most metallic oxides, 64,65 some zincblended semiconductors, 66,67 and metal hydrides. 68 Meanwhile, the band gap values of phase V and two new phases decrease with pressure, the situation is similar to most hydrides.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The band gap value increases rst and then decreases when the P 43m phase transforms into the P4/nmm phase, which is identical to that found in NH 4 I. 15 In the pressure range of phase IV, the band gap increases with increasing pressure, which also occurs in most metallic oxides, 64,65 some zincblended semiconductors, 66,67 and metal hydrides. 68 Meanwhile, the band gap values of phase V and two new phases decrease with pressure, the situation is similar to most hydrides.…”
Section: Resultssupporting
confidence: 72%
“…An ordered phase III only exists in NH 4 Br 12,13 and NH 4 I. 9,11,14 Moreover, we determined the structures of NH 4 I and the related phase transitions at high pressure levels by using ab initio calculations, 15 and found that phase V is stable up to 74 GPa, at which ammonium iodine dissociates into NH 3 , H 2 , and I 2 . Our group 12 also discovered that the phase V of NH 4 Br transforms into monoclinic phase P 2 1 / m at 71 GPa and to orthorhombic structure Cmma at 130 GPa.…”
Section: Introductionmentioning
confidence: 98%
“…[35] The details of convergence tests have been described elsewhere. [36][37][38] 2 presents the formation enthalpy of six phases as a feature of pressure for ScB 4 , and it can be clearly seen that the predicted Cmcm structure is energetically more favorable than the other structures at ambient pressure. As the pressure increases, the Pnma phase becomes the most stable when the pressure is higher than about 18 GPa.…”
Section: Computational Detailmentioning
confidence: 99%
“…In this work, the Sr-Ge binary system under highpressure is systematically studied by using the evolutionary algorithm Universal Structure Predictor: Evolutionary Xtallography (USPEX), which has been successfully used in other systems. [19][20][21][22][23] Six stoichimetric structures (Sr 3 Ge, Sr 2 Ge, SrGe, SrGe 2 , SrGe 3 , and SrGe 4 ) are predicted. In these compounds, Ge atoms present diverse motifs forming covalent boding.…”
Section: Introductionmentioning
confidence: 99%